2014
DOI: 10.5811/westjem.2013.8.17915
|View full text |Cite
|
Sign up to set email alerts
|

Follow Up for Emergency Department Patients After Intravenous Contrast and Risk of Nephropathy

Abstract: Introduction: Contrast-induced nephropathy (CIN), defined as an increase in serum creatinine (SCr) greater than 25% or ≥0.5 mg/dL within 3 days of intravenous (IV) contrast administration in the absence of an alternative cause, is the third most common cause of new acute renal failure in hospitalized patients. It is known to increase in-hospital mortality up to 27%. The purpose of this study was to investigate the rate of outpatient follow up and the occurrence of CIN in patients who presented to the emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…The first is the risk of radiation-induced cancer [18][19][20][21][22], which is theoretically not a major issue in aged patients because of their short expected lifespan. The second is related to intravenous injection of iodinated contrast medium, which is a major concern in aged patients with advanced age, as it is reported to be an independent risk factor for contrast-induced nephropathy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The first is the risk of radiation-induced cancer [18][19][20][21][22], which is theoretically not a major issue in aged patients because of their short expected lifespan. The second is related to intravenous injection of iodinated contrast medium, which is a major concern in aged patients with advanced age, as it is reported to be an independent risk factor for contrast-induced nephropathy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…reported that an iterative reconstruction technique could reduce the radiation dose by 20%–51% and the iodine dose by 40% during abdominal dynamic enhancement CT scanning without deterioration of image quality. Compared with the general population, the reduction in contrast material (CM) provides more benefits because the occurrence of contrast‐induced nephropathy is higher among adrenal and nephrogenic hypertension patients …”
Section: Introductionmentioning
confidence: 99%
“…Compared with the general population, the reduction in contrast material (CM) provides more benefits because the occurrence of contrast-induced nephropathy is higher among adrenal and nephrogenic hypertension patients. 13 The purpose of this study was to assess the effect of a reduced iodine load on contrast enhancement, image quality and detection ability of renal artery stenosis and adrenal lesions in enhancement CT with a combination of an 80 kVp tube voltage setting and ASIR techniques in adrenal and nephrogenic hypertension patients.…”
Section: Introductionmentioning
confidence: 99%
“…CIN is defined as an increase in serum creatinine greater than 25% or ≥ 0.5 mg/dL occurring within 3 days of intravenous contrast agent administration without an alternative cause and is defined as the third cause of hospital-acquired ARF [6]. It is associated with hospitalization, increased length of hospital stay, and high mortality rates [7].…”
Section: Discussionmentioning
confidence: 99%